2020
DOI: 10.1007/s11886-020-01289-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mononuclear Cardiomyocytes in Cardiac Turnover and Regeneration

Abstract: Purpose of Review The typical remodeling process after cardiac injury is scarring and compensatory hypertrophy. The limited regeneration potential of the adult heart is thought to be due to the post-mitotic status of postnatal cardiomyocytes, which are mostly binucleated and/or polyploid. Nevertheless, there is evidence for cardiomyocyte turnover in the adult heart. The purpose of this review is to describe the recent findings regarding the proliferative potential of mononuclear cardiomyocytes and to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Underlying this constrained growth pattern in the zebrafish heart is continuous low-level cardiomyocyte proliferation, which remains throughout adult life, as also observed in the human heart ( Becker and Hesse, 2020 ). The cardiac metrics of ventricular length and compact myocardium thickness, measured in this study, support progressive growth of the heart under this constant proliferation, but it is the emergence of increased programmed cell death from 18 months that appears to halt overall organ growth.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Underlying this constrained growth pattern in the zebrafish heart is continuous low-level cardiomyocyte proliferation, which remains throughout adult life, as also observed in the human heart ( Becker and Hesse, 2020 ). The cardiac metrics of ventricular length and compact myocardium thickness, measured in this study, support progressive growth of the heart under this constant proliferation, but it is the emergence of increased programmed cell death from 18 months that appears to halt overall organ growth.…”
Section: Discussionmentioning
confidence: 74%
“…Importantly, the heart also needs to be able to acutely increase pumping activity in response to a wide range of situations, including injury and infections. Previous studies have shown that throughout life the myocardium exhibits low rates of proliferation, which are concentrated in the mononuclear diploid cardiomyocyte component ( Becker and Hesse, 2020 ). In contrast to other organs, classical stem cell populations do not reside within the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, mononucleated immature cardiomyocytes better preserve their proliferative potential during the postnatal period compared with binucleated counterparts. 64,65 Moreover, rare cardiomyocyte cell cycle events in adult hearts following injury are likely to originate from mononucleated cardiomyocyte. 65 Similarly, inhibition of cardiomyocyte cytokinesis and the subsequent increase in the number of binucleated cardiomyocytes diminishes the proliferative potential of zebra fish and neonatal…”
Section: Key Cellular Characteristics In Pmdmentioning
confidence: 99%
“…64,65 Moreover, rare cardiomyocyte cell cycle events in adult hearts following injury are likely to originate from mononucleated cardiomyocyte. 65 Similarly, inhibition of cardiomyocyte cytokinesis and the subsequent increase in the number of binucleated cardiomyocytes diminishes the proliferative potential of zebra fish and neonatal…”
Section: Key Cellular Characteristics In Pmdmentioning
confidence: 99%
“…The former allows hyperplastic growth, i.e., an increase in the number of cardiomyocytes (cell division and thus, proliferation) while the latter is associated with hypertrophic growth, that is to say an increase in cell size. In this context, it has been shown that cardiomyocyte nucleation and ploidy (the number of complete sets of chromosomes, n ) is critical ( 34 ). Indeed, mononucleated diploid cardiomyocytes have a lot more options regarding their future than tetraploid or binucleated cardiomyocytes ( Figure 4 ).…”
Section: Mechanisms Underlying Heart Regenerationmentioning
confidence: 99%